Quarto de despejo and Olhos d’água: awakening from an unjust sleep: - Lima, Bruna Everlyn Bitencourt de; Farias, Thyago Martins de; Cassin, Márcia Pereira da Silva (Argumentum, 2024)
The article aims to shed light on the role of literature in the interpretation of Brazilian social formation, with greater emphasis on the racial issue. Prepared from qualitative bibliographic research, it initially seeks to address the relationship between literature and society. Next, it develops a reflection on the implications of racism and the myth of racial democracy on the genocide of the black population and demonstrates how the writing of Carolina Maria de Jesus and Conceição Evaristo denounces this reality and points out paths of resistance. The results indicate the potential of literature and the literary works analyzed as instruments of social criticism and analysis of Brazilian reality.